2004
DOI: 10.1111/j.1538-7836.2004.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effects of drotrecogin alfa (activated) in patients with severe sepsis with or without overt disseminated intravascular coagulation

Abstract: To cite this article: Dhainaut J-F, Yan SB, Joyce DE, Pettilä V, Basson B, Brandt JT, Sundin DP, Levi M. Treatment effects of drotrecogin alfa (activated) in patients with severe sepsis with or without overt disseminated intravascular coagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
243
0
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(263 citation statements)
references
References 16 publications
10
243
0
10
Order By: Relevance
“…However, the post‐hoc subgroup analyses of those RCTs indicated that the anticoagulant therapies resulted in improved mortality rates in patients with sepsis‐induced DIC 8, 9. In Japan, anticoagulant therapy has been approved for use as adjunctive therapy for patients with sepsis‐induced DIC and is now widely applied in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, the post‐hoc subgroup analyses of those RCTs indicated that the anticoagulant therapies resulted in improved mortality rates in patients with sepsis‐induced DIC 8, 9. In Japan, anticoagulant therapy has been approved for use as adjunctive therapy for patients with sepsis‐induced DIC and is now widely applied in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Response to corticotropin test for corticosteroids in septic shock (59) IL-6 level for monoclonal anti-tumor necrosis factor in sepsis ( mortality but also showed a trend toward greater RRR with activated protein C treatment (29 vs. 18%, P = 0.26) (43). An ongoing phase III study of a related therapy-recombinant human thrombomodulin-now requires evidence of disseminated intravascular coagulation for study enrollment (44).…”
Section: Identifying Biomarkers To Use For Predictive Enrichmentmentioning
confidence: 99%
“…5 DIC may lead to microvascular thrombosis, causing multiple organ dysfunctions, and it is conceivable that a prothrombotic disposition such as FVL would be associated with an increased rate of fibrin disposition, causing organ dysfunction and death in sepsis.…”
Section: Introductionmentioning
confidence: 99%